Effects of High CO2Contents on the Biogas/Diesel RCCI Combustion at Full Engine Load - Dalha, I.B. (Joint Journal of Novel Carbon Resource Sciences and Green Asia Strategy, 2022)
Disparities in the constituents among biogases pose various control challenges during combustion, thus complicating its operability. Improving biogas by eliminating carbon dioxide (CO2) remains difficult, and high CO2concentration is known to affect combustion. Still, the effect on Biogas/Diesel dual-fuel reactivity-controlled compression ignition (RCCI) combustion is not well explored. The influence of high diluent (CO2) proportions (25 - 45) and Biogas fraction (40 - 70) on Biogas/Diesel dual-fuel RCCI combustion was evaluated experimentally, at full load and 1600 rpm. The results show distinct temperature trends across the combustion regimes for all the CO2ratios and Biogas fractions. The radiation absorption effect of high CO2reduces the cylinder temperature and delays the expansion to a 10 - 20o crank angle after the top dead centre (CA ATDC). The temperature and pressure decrease with the increase in CO2ratios and Biogas fractions, unlike heat released rate. Burning Diesel and 45 CO2indicate the fastest combustion, with combustion phasing (CA50) at 6.353 ms ATDC while 25 and 35 CO2were slowed by 0.258 and 0.578 ms, respectively. Inferentially, 35 CO2at a fraction of 50 could form the best reactivity. Â© 2022 Novel Carbon Resource Sciences. All rights reserved.